2019
DOI: 10.1590/1414-431x20198409
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl isothiocyanate inhibits invasion and induces apoptosis via reducing S100A4 expression and increases PUMA expression in oral squamous cell carcinoma cells

Abstract: Benzyl isothiocyanate (BITC) has been shown to inhibit invasion and induce apoptosis of various types of cancer. However, its role on human oral squamous cell carcinoma (OSCC) cells is still not well elucidated. In the present study, we investigated the effect of BITC on apoptosis and invasion of SCC9 cells, and its underlying mechanisms in vitro and in vivo . SCC9 cells were exposed to BITC (5 and 25 μM) for 24 and 48 h. Cell growth, apoptosis, invasion, and migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Salvadora persica is a reliable natural supply for extracting benzyl isothiocyanate (BITC) that is believed to be promising within the development of anticancer medications. Recently, BITC found to inhibit prostate cancer [11], lung cancer [12], oral cancer [13], and invasion of hepatocellular carcinoma [14].…”
Section: Introductionmentioning
confidence: 99%
“…Salvadora persica is a reliable natural supply for extracting benzyl isothiocyanate (BITC) that is believed to be promising within the development of anticancer medications. Recently, BITC found to inhibit prostate cancer [11], lung cancer [12], oral cancer [13], and invasion of hepatocellular carcinoma [14].…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptome analysis revealed several genes, which are associated with the regulation of cell survival such as S100A4 and SYK, both of which were upregulated in EJ28P. Incidentally, S100A4 expression is positively regulated by the Wnt/β-catenin signalling pathway [ 40 ] to protect cells from pro-apoptotic stimuli [ 41 , 42 ]. It was reported that the knockdown of S100A4 decreased cellular proliferation and promoted apoptosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of isothiocyanates (ITCs), which are natural compounds found in crucifer vegetables, has been proposed. These ITCs are related to anti-proliferative and apoptotic activity, as they are capable of destabilizing the mitochondrial membrane and inducing apoptosis by the increase in Bax and the inhibition of Bcl-2 and Bcl-XL [ 181 , 182 ]. Ma et al evaluated the activity of Benzyl isothiocyanate and found that this ITC is capable of promoting apoptosis by the induction of caspase-3 and inhibiting the expression of MMP9, which is related to the induction of EMT [ 182 ].…”
Section: Inhibition Of Emt Is Important In the Treatment Of Hnsccmentioning
confidence: 99%